2004
DOI: 10.1158/1078-0432.ccr-04-0181
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Tumor-Specific Humoral and Cellular Immune Responses to NY-ESO-1 in Hepatocellular Carcinoma

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 37 publications
2
97
1
Order By: Relevance
“…We also confirmed that SPACA3/SLLP1, SPANXB, and the MAGE-A, GAGE, CTAG, and SSX gene families are expressed by MMC (20,29,31,32,(41)(42)(43)(44). The CT Ag CTAG1B/ NY-ESO-1, known to be highly immunogenic (27,45,46), shows the highest median signal in MMC compared to the testis with a frequency of presence of 13% in MM patients, which is lower than the frequency observed by van Rhee et al (31).…”
Section: Discussionmentioning
confidence: 86%
“…We also confirmed that SPACA3/SLLP1, SPANXB, and the MAGE-A, GAGE, CTAG, and SSX gene families are expressed by MMC (20,29,31,32,(41)(42)(43)(44). The CT Ag CTAG1B/ NY-ESO-1, known to be highly immunogenic (27,45,46), shows the highest median signal in MMC compared to the testis with a frequency of presence of 13% in MM patients, which is lower than the frequency observed by van Rhee et al (31).…”
Section: Discussionmentioning
confidence: 86%
“…This feature is one of the innovative notions in this study. Previous observations show that antibodies to any individual antigen such as p53 [8,30], c-myc [30,33], p62 [30] or NY-Eso-1 [34] do not reach levels of sensitivity which could become routinely useful in diagnosis. Recent studies indicate that combinations of multiple antigen-antibody systems may acquire higher sensitivity for diagnosis of cancer [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies of patients with advanced breast or ovarian cancer have shown that when Th epitopes are combined with CTL epitopes they provide a more powerful and longer lasting immunity than CTL epitopes alone (30,31). Although there have been single reports of CD4 ϩ responses to both AFP and cancer testis Ags in HCC patients (12,32), there is a need to characterize the epitopes recognized by Th cells for future use in peptide vaccination studies.…”
Section: Discussionmentioning
confidence: 99%